ACE inhibitory activity in vitro and antihypertensive effect in vivo of LSGYGP and its transepithelial transport by Caco-2 cell monolayer. (October 2019) - Tianrui, Zhao; Bingtong, Liu; Ling, Yuan; Liping, Sun; Yongliang, Zhuang
Graphical abstract: Highlights: The IC50 value of ACEI activity of LSGYGP in vitro was 25.74 μM. The ACEI kinetic of LSGYGP was noncompetitive. LSGYGP had a high binding affinity with ACE sites by seven short hydrogen bonds. LSGYGP had a good antihypertensive effect in vivo and lung was a key target tissue. LSGYGP could be absorbed by Caco-2 cell monolayer, and partly degraded or modified. Abstract: Leu-Ser-Gly-Tyr-Gly-Pro (LSGYGP) was obtained in our previous study. The angiotensin I-converting enzyme inhibitory (ACEI) activity in vitro and the antihypertensive effect in vivo of LSGYGP were determined in this study. The IC50 value of ACEI activity of LSGYGP was 25.74 μM, and the ACEI kinetic was noncompetitive. LSGYGP showed a high binding affinity with ACE sites by using seven short hydrogen bonds. LSGYGP had a clear antihypertensive effect on spontaneously hypertensive rats, and the systolic blood and diastolic blood pressures remarkably decreased by 19.81% and 29.92% in 3 h of administration. The ACE activities of serum, kidneys, and lungs were determined at different times, and lung was evaluated as the key target tissue. LSGYGP was completely absorbed by Caco-2 cell monolayer, and the transport degree was 3.5%. Furthermore, several degradations and modifications of LSGYGP, such as SGYGP, LSGY, GYGP, LSGYP, LSSGYGP, and LSLSGYGP, were found during the transport process.